Dirofilaria immitis and D. repens show circadian co-periodicity in naturally co-infected dogs - Ionică, Angela Monica; Matei, Ioana Adriana; D'Amico, Gianluca; Bel, Lucia Victoria; Dumitrache, Mirabela Oana; Modrý, David; Mihalca, Andrei Daniel (Parasites & vectors, 2017)
BACKGROUND: Dirofilaria immitis and Dirofilaria repens are mosquito-borne zoonotic filarioids typically infecting dogs, causing a potentially fatal cardiopulmonary disease and dermatological conditions, respectively. The females are larviparous, releasing the larvae (microfilariae) into the bloodstream, which further develop in mosquito vectors. However, microfilaremia greatly fluctuates during a 24-h period. As the sampling time can greatly influence the accuracy of diagnosis, the aim of the present study was to assess the circadian periodicity of D. immitis and D. repens in naturally co-infected dogs in an endemic area of Romania and to investigate possible differences of periodicity between these two species. METHODS: Overall, four dogs harbouring natural co-infection with D. immitis and D. repens were selected and sampled every two hours for two consecutive days: two dogs in July 2014 and two in July 2015. At each sampling time, a 0.7 ml blood sample was taken. Modified Knott's test was performed on 0.5 ml, and the remaining 0.2 ml were used for DNA extraction and molecular amplification, both in single and duplex PCR reactions. Microfilariae of both species were morphologically identified and counted in each collected sample, microfilaremia was calculated, and fluctuation was charted. RESULTS: The dynamics of microfilaremia showed similar patterns for both Dirofilaria species. In all four dogs, D. immitis was present at all sampling times, with several peak values of microfilaremia, of which one was common for all dogs (1 am), while minimum counts occurred between 5 and 9 am. Similarly, for D. repens, one of the peak values was recorded in all dogs at 1 am, while minimum counts (including zero) occurred at 9 and 11 am. Single species-specific PCR reactions were positive for both D. immitis and D. repens in all collected samples, while duplex PCR failed to amplify D. repens DNA in many cases. CONCLUSIONS: Both Dirofilaria immitis and D. repens microfilariae are subperiodic, following a similar variation pattern, with peak values of microfilaremia registered during the night in Romania. Duplex PCR fails to identify the infection with D. repens in co-infected dogs when the ratio of microfilaremia is in favour of D. immitis.
Keywords: koinfekce; druhová specificita; Animals; Dog Diseases; Dogs; Circadian Rhythm; nemoci psů; Parasitemia; zvířata; dirofilarióza; Dirofilariasis; Coinfection; psi; Romania; Dirofilaria repens; Dirofilaria immitis; Polymerase Chain Reaction; polymerázová řetězová reakce; Rumunsko; parazitemie; cirkadiánní rytmus; Species Specificity